The pain experience and cooperation of patients in consecutive cataract surgery - ÇEKİÇ, OSMAN (SAGE PUBLICATIONS LTD, 2013)
PURPOSE. The aim of this study was to investigate the pain experience and the cooperation of patients during consecutive cataract surgery. METHODS. In this prospective, randomized study, 60 consecutive adult patients with bilateral senile cataracts were recruited. All operations were performed with clear corneal phacoemulsification (phaco) technique under topical and intracameral anesthesia without sedation. The first surgery was performed in the eye with high-grade cataract. The other eye was operated within 3 months. Every patient was graded using a visual analogue scale (VAS) from 0 (no pain) to 10 (unbearable pain) after the surgery. The cooperation of the patient was graded from 0 (no event) to 3 (marked eye and head movement and lid squeezing) by the surgeon. The VAS scores and cooperation of patients were the main outcome measurements. RESULTS. The mean VAS score was 1.50 +/- 0.81 in the first surgery and 2.15 +/- 0.79 in the other eye surgery (p<0.001). The patient cooperation score was 1.50 +/- 0.81 in the first surgery and 2.18 +/- 0.77 in the other eye surgery (p<0.001). The VAS and patient cooperation scores were positively correlated (r=0.633, p<0.001) in the study group. The VAS and patient cooperation scores were similar based on sex and laterality. CONCLUSIONS. Patients who previously underwent phaco surgery in one eye experience more pain and have worse cooperation during the other eye phaco surgery.
Keywords: Consecutive cataract surgery; Cooperation of patient; Pain experience; TOPICAL ANESTHESIA; INTRACAMERAL ANESTHESIA; PHACOEMULSIFICATION; PERCEPTION; GENDER